MODEL OF PREGNANCY EXERCISE WITH DURATION IN THE FIRST STAGE OF LABOR IN PRIMIPARA - Mahanani Mulyaningrum; Yuwanti (Jurnal Profesi Bidan Indonesia, 2023)
Background : Pregnancy exercise is a movement exercise therapy to maintain maternal stamina and fitness during pregnancy and prepare pregnant women physically and mentally to face childbirth optimally. Some of the advantages of pregnancy exercise are decreased energy use, reduced pain, fiber improves APGAR Score and fetal psychomotor. Methodology : This study uses quantitative methods. The design of this study was an observational study with a cross-sectional design. Data analysis of 2 groups in pairs using the Chi Square test. Results : he result of using the Gamma test is that the p value is 0.000, which means that there is a relationship between pregnancy exercise and the duration of the first stage of labor in primiparous mothers in the work area of the Tanggungharjo public health center. Conclusion : There is a relationship between pregnancy exercise and the duration of the first stage of labor in primiparous mothers in the work area of the Tanggungharjo public health center